2016
DOI: 10.1371/journal.pone.0148322
|View full text |Cite
|
Sign up to set email alerts
|

Digit Sucking Habit and Association with Dental Caries and Oral Hygiene Status of Children Aged 6 Months to 12 Years Resident in Semi-Urban Nigeria

Abstract: ObjectivesNon-nutritive sucking (NNS) is a common behavior in childhood. The association between digit sucking, dental caries and oral health has been studied with inconclusive results. The objectives of this study were to determine the prevalence of, and the association between digit sucking, caries and oral hygiene status of children age six months to 12 years, resident in Ile-Ife, Osun State, Nigeria.MethodsA cross-sectional study was conducted in Ife Central Local Government Area of Osun State. Data were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 31 publications
4
28
2
Order By: Relevance
“…The household factors did not show significant associations with the occurrence and severity of caries in children within or between the groups. This observation is contrary to what other studies have found in rural setting . Children from low socio‐economic status background were not likely to access oral hygiene aids and therefore more prone to caries .…”
Section: Discussioncontrasting
confidence: 98%
“…The household factors did not show significant associations with the occurrence and severity of caries in children within or between the groups. This observation is contrary to what other studies have found in rural setting . Children from low socio‐economic status background were not likely to access oral hygiene aids and therefore more prone to caries .…”
Section: Discussioncontrasting
confidence: 98%
“…This study was a sub-study of a primary study that determined the association between digit sucking, caries and periodontitis in 6-months-olds to 12-year-olds resident in Ile-Ife [43]. The primary data were collected through a household survey using a three-level cluster sampling procedure.…”
Section: Methodsmentioning
confidence: 99%
“…Radiographs were not used in this study. The intraexaminer correlation scores ranged between 0.89-0.94, while inter-examiner kappa Cohen scores ranged between 0.82-0.90 for caries detection and OHI-S [43,44]. The dmft score was obtained by adding the d, m and f scores for each child less than 6 years of age.…”
Section: Cariogenic Dietmentioning
confidence: 99%
“…This report is part of a large study determining factors associated with NNS habits. Part of this study has been previously reported by Kolawole et al 23 Nine hundred and ninety‐two participants (508 [51.2%] males and 484 [48.8%] females, aged 1 to 12 years; mean age [± 95% confidence interval (CI)]: 5.83 [± 3.15] years; modal age: 3 years [12.3%]) who met the inclusion criteria were recruited for this study.…”
Section: Methodsmentioning
confidence: 99%
“…Recruitment continued in enumeration sites until the study sample per data collector was reached. Details of the sampling and data collection process has been reported by Kolawole et al 23 …”
Section: Methodsmentioning
confidence: 99%